Pengaruh Pajak Hotel, Pajak Penerangan Jalan dan Pajak Hiburan Terhadap Pendapatan Asli Daerah Kabupaten Boyolali - Yulia Wulan Dari; Rukmini; LMS Kristiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the Effect of Hotel Tax, Street Lighting Tax, and Entertainment Tax on the Original Regional Income (PAD) of Boyolali Regency. This study uses a quantitative method with data from the Regional Finance Agency (BKD) of Boyolali Regency for the period 2021 - 2024. The results of this study indicate that Hotel Tax does not have a significant effect on the PAD of Boyolali Regency, with a value of 0.075. Similar to Entertainment Tax, the results of the Entertainment Tax study also have no significant effect on the PAD of Boyolali Regency. In contrast to Street Lighting Tax, the results show that Street Lighting Tax has a significant effect on the PAD of Boyolali Regency. Based on these results, the study recommends that local governments optimize tax management and increase public awareness of the importance of paying taxes.